Clinical, lipid-lowering, and pleiotropic effectiveness of rosuvastatin: a review of the GALAXY programme results - A. N. Britov; M. P. Chupina (Кардиоваскулярная терапия и профилактика)
The paper reviews the results of the GALAXY international programme, a series of clinical (mostly comparative) studies of various statins. It has demonstrated the benefits of rosuvastatin in terms of normalization of lipid profile, inflammatory markers, and coronary or cerebrovascular atherosclerosis regression. This makes rosuvastatin medications promising for the prevention of severe organ complications at all atherosclerosis stages.